2016
DOI: 10.1016/j.nima.2016.02.050
|View full text |Cite
|
Sign up to set email alerts
|

Measured and simulated heavy-ion beam loss patterns at the CERN Large Hadron Collider

Abstract: a b s t r a c tThe Large Hadron Collider (LHC) at CERN pushes forward to new regimes in terms of beam energy and intensity. In view of the combination of very energetic and intense beams together with sensitive machine components, in particular the superconducting magnets, the LHC is equipped with a collimation system to provide protection and intercept uncontrolled beam losses. Beam losses could cause a superconducting magnet to quench, or in the worst case, damage the hardware. The collimation system, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 11 publications
(22 reference statements)
0
18
0
Order By: Relevance
“…In this article we present predictions for HL-LHC losses during luminosity levelling, as well as measurements of the performance of the LHC collimation system during Run 1 and 2. Previously, studies of LHC collimation efficiency have been successfully performed using the * sam.tygier@manchester.ac.uk SixTrack code with comparisons to BLM data at fixed optical configurations [7][8][9][10][11][12][13][14][15]. These demonstrate that maps of proton loss locations are useful for evaluating collimation scenarios and as input to energy deposition studies using codes such as FLUKA [16].…”
Section: Introductionmentioning
confidence: 99%
“…In this article we present predictions for HL-LHC losses during luminosity levelling, as well as measurements of the performance of the LHC collimation system during Run 1 and 2. Previously, studies of LHC collimation efficiency have been successfully performed using the * sam.tygier@manchester.ac.uk SixTrack code with comparisons to BLM data at fixed optical configurations [7][8][9][10][11][12][13][14][15]. These demonstrate that maps of proton loss locations are useful for evaluating collimation scenarios and as input to energy deposition studies using codes such as FLUKA [16].…”
Section: Introductionmentioning
confidence: 99%
“…-18 - The HEL performance assessment relies on multi-turn tracking simulations carried out with SixTrack [42][43][44][45][46] that allows a symplectic, fully chromatic, and 6D tracking along the magnetic lattice of the machine, taking into account interactions with the ring collimators and the detailed aperture model of the entire ring. The code has been compared to LHC data in a number of studies [4,7,11,[47][48][49][50] with excellent agreement. HELs are integrated in the lattice as magnetic elements [51,52] and their effect on the beam can be modelled using different electron beam kicks (earlier studies can also be found in [53,54]).…”
Section: Expected Performancementioning
confidence: 99%
“…Adapted with permission. [ 374 ] The separation between the beams is exaggerated here (in reality it is 20 cm). IP: interaction points.…”
Section: Colliding‐beam Opportunitiesmentioning
confidence: 99%